On the Use of FTAs: A Review of Research Methodologies - Shintaro Hamanaka (Asian Development Bank (ADB), 2013)
There has been much confusion, rather than debate, on the use of free trade agreements (FTAs). Unfortunately, a large part of the confusion is caused by the absence of consensus on the meaning of key terms such as the "utilization rate" and "usage rate" of FTAs, and the lack of knowledge on upward or downward biases from various information sources regarding the use of FTAs. Rather than making an original empirical contribution, this article reviews existing studies on the issue and attempts to identify the relevant methodologies for assessing the use of FTAs.
hdl:11540/2097
Keywords: F13; F15; 330; Free trade agreements (FTAs); utilization of FTAs; impacts of FTAs; margin of preference (MoP)